2021
DOI: 10.1177/00953997211025984
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Local Public Policies for Economic Development and Entrepreneurial Presence: The Italian Case

Abstract: The financial crisis has made the theme of economic development particularly significant. Analysis of this topic cannot ignore a key actor, that is, public administration. Here, we focus on all the Italian municipalities ( n = 7,978), analyzing the relationship between local public policies (in terms of municipalities’ governance and local governments’ financial engagement) supporting urban economic development and local entrepreneurial presence (total number of active firms). Applying the general least square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Minniti (2008) as well as Ferrell and Fraedrich (2021) claim that policymakers shape the business environment by the active support of new and existing business entities through various entrepreneurship policies (Stevenson & Lundström, 2001). De Matteis et al (2022) as well as Dvouletý and Lukeš (2016) discuss impact of public policies on entrepreneurship. In their opinion, policies focused on self-employed may lead to higher levels of entrepreneurial activity.…”
Section: New-business Formation Factorsmentioning
confidence: 99%
“…Minniti (2008) as well as Ferrell and Fraedrich (2021) claim that policymakers shape the business environment by the active support of new and existing business entities through various entrepreneurship policies (Stevenson & Lundström, 2001). De Matteis et al (2022) as well as Dvouletý and Lukeš (2016) discuss impact of public policies on entrepreneurship. In their opinion, policies focused on self-employed may lead to higher levels of entrepreneurial activity.…”
Section: New-business Formation Factorsmentioning
confidence: 99%
“…(Megawati et al, 2023) found that tourism growth directly influences public well-being but didn't explore how it mediates the relationship between government policies and well-being. (De Matteis et al, 2022) noted a link between supportive government policies and development but didn't delve into the direct impact on public well-being. Lastly, (Pranita et al, 2022) identified tourism growth as a mediator between government policies and public well-being, albeit focusing on only one aspect of those policies.…”
Section: Introductionmentioning
confidence: 99%